2018
DOI: 10.3892/mmr.2018.8402
|View full text |Cite
|
Sign up to set email alerts
|

Ubenimex, an APN inhibitor, could serve as an anti‑tumor drug in RT112 and 5637 cells by operating in an Akt‑associated manner

Abstract: Bladder cancer, a common urinary tract tumor, has high mortality and recurrence rates associated with metastasis. Aminopeptidase N (APN) expression and metastasis have been indicated to be associated with one another. Ubenimex may function as an APN inhibitor to inhibit the degradation of the extracellular matrix during tumorigenesis. Furthermore, APN has been widely used as an adjuvant therapy for the treatment of tumors; however, little information is available regarding the impact of ubenimex on patients. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…On the basis of this concept, a number of studies have been performed to investigate the therapeutic potential of autophagic cell death activation in different fields of cancer treatment. In BC, autophagic cell death has been noted in chemotherapy with pazopanib (57), biological therapy with Cheliensisine A-fluoride (ChlA-F) (58) and with alternative therapies (59,60,75) (Table II).…”
Section: Autophagy Regulation In Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of this concept, a number of studies have been performed to investigate the therapeutic potential of autophagic cell death activation in different fields of cancer treatment. In BC, autophagic cell death has been noted in chemotherapy with pazopanib (57), biological therapy with Cheliensisine A-fluoride (ChlA-F) (58) and with alternative therapies (59,60,75) (Table II).…”
Section: Autophagy Regulation In Bcmentioning
confidence: 99%
“…Therefore, as an APN inhibitor, ubenimex is a promising agent for cancer treatment. Ubenimex has been shown to inhibit the proliferation, migration and invasion of BC cells by downregulating APN expression levels and inducing autophagy through inhibition of the Akt signaling pathway (75). On the contrary, autophagy inhibition with 3-MA reversed the antiproliferative properties of ubenimex, indicating that ubenimex was capable of inducing autophagic cell death in BC cells (75).…”
Section: Autophagy Regulation In Bcmentioning
confidence: 99%
“…Previous studies have demonstrated that ubenimex can induce not only apoptosis but also autophagic cell death in malignant melanoma and bladder cancer cells 22,23. In the present study, we directly detected autophagosome formation by transmission electron microscopy.…”
Section: Resultsmentioning
confidence: 70%
“…Previous reports have found that ubenimex shows cytotoxicity and suppresses cell proliferation in leukaemia cell lines,27 glioma,28 malignant melanoma and bladder cancer 22,23. In addition, ubenimex can also synergistically enhance the efficacy of anticancer drugs in many human tumour-derived cell lines, such as those from hepatocellular carcinoma and osteosarcoma 2931.…”
Section: Discussionmentioning
confidence: 99%
“…62 APN is a cell membrane protein that is responsible for digesting peptides generated by gastric and pancreatic proteases. 63 Due to its extracellular localization and overexpression in bladder cancer (BC), 64,65 APN activity is an attractive target for the diagnosis and staging of BC. Other NIR-I dyes have been reported for APN, 66,67 but in addition to the APN trigger and a NIR-I dye, the probe developed by the authors (CyP1) is also equipped with a renal clearance moiety (Fig.…”
Section: Near Infrared-i Fluorescencementioning
confidence: 99%